2013
DOI: 10.1179/1743676112y.0000000066
|View full text |Cite
|
Sign up to set email alerts
|

Advanced indium tin oxide ceramic sputtering targets (rotary and planar) for transparent conductive nanosized films

Abstract: Indium tin oxide (ITO) ceramic sputtering targets used for the manufacturing of transparent conductive thin films for electrodes in flat panel displays, solar cells, touch panels, antistatic films and others developed and commercially produced are described. Thanks to optimised compositions and developed technology, commercially producing large size planar and new generation rotary ceramic target components have high density (up to 99?5% of theoretical density), uniform microcrystalline structure and superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The pressures most frequently reported for LCO deposition are rather high compared to those used to deposit other materials. For example, indium tin oxide films, which are widely used as transparent electrodes in touch screens and solar cells, are typically sputter deposited at pressures between 0.3 Pa and 0.6 Pa [41]. Lowering the pressure for LCO deposition may increase the deposition rate and reduce gas consumption, but previous studies have shown that it could also increase the volume fraction of Co3O4 and concentration of lithium in excess of its stoichiometric value [2,18,21,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The pressures most frequently reported for LCO deposition are rather high compared to those used to deposit other materials. For example, indium tin oxide films, which are widely used as transparent electrodes in touch screens and solar cells, are typically sputter deposited at pressures between 0.3 Pa and 0.6 Pa [41]. Lowering the pressure for LCO deposition may increase the deposition rate and reduce gas consumption, but previous studies have shown that it could also increase the volume fraction of Co3O4 and concentration of lithium in excess of its stoichiometric value [2,18,21,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…As we believe, SPS sintering of the ZnO-In 2 O 3 system in vacuum took place in a reducing atmosphere with the participation of reactive indium hemioxide due to the use of graphite tooling (punch and matrix of the press-form, sealing materials). This can explain the rapid formation of the new homologous In 2 Zn 5 O 8 phase at the SPS temperature of 950 Thus, all synthesized ceramic samples had sufficient physical density and good electrical conductivity for their further use as targets in the formation of homogeneous thin films by dc magnetron sputtering [21]. It should be noted that all targets sputtered for more than 3 h retained their integrity (Figure S2 of SM).…”
Section: Resultsmentioning
confidence: 83%
“…In addition, by the addition of SnO 2 to In 2 O 3 , the indium tin oxide ceramics, which is one of the most reliable and suitable materials for sputtering targets for the production of highly transparent and electrically conductive oxide thin films by conventional direct current magnetron sputtering, have been formed. 12 So far, SnO 2 has been used to photocatalytic decontamination treatment of polluted water. [13][14][15] However, most of the ongoing research on SnO 2 photocatalysis focuses on the use of nanocrystalline powder.…”
Section: Introductionmentioning
confidence: 99%